Enantioselective toxic effects and digestion of furalaxyl enantiomers in Scenedesmus obliquus. Issue 12 (20th September 2018) - Cheng, Cheng; Ma, Rui; Lu, Yuele; Liu, Chunxiao; Zhang, Wenjun; Di, Shanshan; Chen, Li; Diao, Jinling; Zhou, Zhiqiang; Hou, Yuxia
Abstract: Research on the enantioselective environmental behavior of chiral pesticides has been a hot spot of environmental chemistry recently. In this study, the acute toxicity and digestion of furalaxyl enantiomers were determined on the aquatic algae Scendesmus obliquus. After exposure for 96 hours, the EC50 values for (S)‐furalaxyl and (R)‐furalaxyl were 13.59 and 15.26 mg/L, respectively. In addition, enantioselectivity was observed from the determined chlorophyll contents and antioxidant enzyme (CAT and SOD) activities of algae cells after exposure to furalaxyl enantiomers for 96 hours. The digestion rate of (S)‐furalaxyl and (R)‐furalaxyl were almost the same in S. obliquus . On the basis of these data, the inactive enantiomers (S)‐ furalaxyl is more toxic than the active one on the non‐target species S. obliquus, indicating that such enantiomeric differences should be taken into consideration in the study of pesticide risk assessment. Abstract :